1994
DOI: 10.1001/archinte.1994.00420190058007
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Susceptibility Patterns, Predictors of Multidrug Resistance, and Implications for Initial Therapeutic Regimens at a New York City Hospital

Abstract: Tuberculosis isolates at our hospital have a high frequency of multidrug resistance. Only five- or six-drug regimens are theoretically adequate as initial therapy for our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…We matched cases and controls for gender and age bracket, considering that those variables could act as confusing factors, since the results found in the literature are rather discrepant regarding those two characteristics (21,22) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We matched cases and controls for gender and age bracket, considering that those variables could act as confusing factors, since the results found in the literature are rather discrepant regarding those two characteristics (21,22) .…”
Section: Resultsmentioning
confidence: 99%
“…The controversy started with the CDC publication on the MDR-TB outbreak among HIV-infected subjects in New York and Miami. Several investigators associated MDR-TB with HIV (22) , others showed that there was no association whatsoever (29,30) . In 1998, Spellman et al published a study conducted with the purpose of comparing the prevalence of MDR-TB among patients with and without HIV infection, to settle the matter; they concluded that HIV infection was not a risk factor for MDR-TB (31) .…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in the United States discovered that HIV infection was also a risk factor for resistance [9][10][11][12][13]. Other risk factors reported included foreign birth, ethnicity, living in urban centers, and having cavitary pulmonary tuberculosis [9,11,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…HIV has been found to be a risk factor for resistance in the United States [5,[7][8][9] but not in Africa [10]. Some studies have found resistance to be associated with cavitatory pulmonary disease [11], and most studies from developed countries (particularly the United States) have found relationships with ethnic groupings [5,7], foreign birth [7,[12][13][14] and urban centres [13]. In the United Kingdom surveillance data from England and Wales have generally shown an excess of drug-resistant cases in London, in HIV-positive cases, those not born in the United Kingdom and sometimes in non-white ethnic groups [2,3,15].…”
Section: Introductionmentioning
confidence: 99%